The theory of the Parry-Lord in the study of poetry zhyrau XV-XVIII centuries (Eurasian Journal of Philology Science and Education, 2016)
The article examines in detail the influence of the school of Parry-Lord in the Kazakh epic poetry. For example, basic research B.S. Abylkasimov we consider the essence, the origin of epic formulas as stylistic and formal-stylistic and artistic patterns and signs of an oral-style techniques, such as formula, stability, constancy in the position of individual words, stereotypes, syntactic uniformity of content and stylistic units. Article is mainly to the discussion. It contains examples, as confirming the main findings of the concept of the Parry-Lord and developing them in the desired direction – the origin of the epic, epic formulas, text zhyrau overall, rising to ancient folklore, myth, rite and ritual. Based on the general criticism of the monograph researcher B.S. Abylkasimova, we come to a constructive solution – zhyrau and Akins all their various poetic system, different social function of the text, a variety of orally-style «formula» technique, so the most important question here is the question of the differentiation of genres in relation to their social functions and Genesis.
Keywords: improviser; oral; stylistic technique; the epic formula; rhythm; epic; epic poetry folklore; genre; plot; myth; rite; ritual; primordial tradition; the cult of ancestors; constructive criticism.